PENGARUH MODEL CONCEPT ATTAINMENT BERBANTUAN MEDIA VIMABA TERHADAP PEMAHAMAN KONSEP SISWA KELAS IV SD HARJOSARI 01 - Waruwu, Akwilan; Purwanti, Kartika Yuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT Students' conceptual understanding is an essential competency in elementary education. However, observations at SD Negeri Harjosari 01 indicated that students' conceptual understanding remained low due to teacher-centered instruction and the limited use of interactive learning media. This study aimed to determine the differences and the effect of the Concept Attainment learning model assisted by Vimaba (Interactive Video) media on the conceptual understanding of fourth-grade students. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The sample consisted of 53 students, including 27 students in the experimental class and 26 students in the control class. Data were collected through conceptual understanding tests, observations, interviews, questionnaires, and documentation. Data analysis was conducted using the Independent Sample t-test and simple linear regression with the assistance of IBM SPSS Statistics 26. The results showed that the experimental class achieved a higher posttest mean score (88.26) than the control class (76.65). The Independent Sample t-test indicated a significance value of 0.000 (<0.05), confirming a significant difference between the two groups. Furthermore, the simple linear regression analysis produced an F-value of 50.292 with a significance value of 0.000 (<0.05), indicating that the Concept Attainment learning model assisted by Vimaba media had a significant positive effect on students' conceptual understanding. Therefore, the Concept Attainment learning model assisted by Vimaba media can be used as an effective alternative to improve elementary school students' conceptual understanding. Keywords: Concept Attainment, Vimaba Interactive Video, Conceptual Understanding, Elementary School ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep siswa kelas IV SD Negeri Harjosari 01 yang disebabkan oleh pembelajaran yang masih berpusat pada guru dan terbatasnya penggunaan media pembelajaran interaktif. Penelitian ini bertujuan untuk mengetahui perbedaan serta pengaruh penggunaan model pembelajaran Concept Attainment berbantuan media Vimaba (Video Interaktif) terhadap pemahaman konsep siswa. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi experiment tipe nonequivalent control group design. Sampel penelitian berjumlah 53 siswa yang terdiri atas 27 siswa kelas eksperimen dan 26 siswa kelas kontrol. Teknik pengumpulan data meliputi tes pemahaman konsep, observasi, wawancara, angket, dan dokumentasi. Analisis data dilakukan menggunakan uji Independent Sample t-test dan regresi linear sederhana dengan bantuan IBM SPSS Statistics 26. Hasil penelitian menunjukkan bahwa rata-rata nilai posttest kelas eksperimen sebesar 88,26 lebih tinggi dibandingkan kelas kontrol sebesar 76,65. Hasil uji Independent Sample t-test memperoleh nilai signifikansi 0,000 (<0,05), yang menunjukkan adanya perbedaan yang signifikan antara kedua kelas. Selain itu, hasil uji regresi linear sederhana menunjukkan nilai F sebesar 50,292 dengan signifikansi 0,000 (<0,05), sehingga dapat disimpulkan bahwa model pembelajaran Concept Attainment berbantuan media Vimaba berpengaruh signifikan terhadap pemahaman konsep siswa. Dengan demikian, model pembelajaran tersebut dapat dijadikan sebagai alternatif pembelajaran untuk meningkatkan pemahaman konsep siswa sekolah dasar. Kata Kunci: Concept Attainment, media Vimaba, pemahaman konsep, sekolah dasar